Comparative Evaluation of Efficacy of Herbal and Chlorhexidine Mouthwash on Gingival Health - Vaishnavi Senkalvarayan; Priya Kesavan; Jayachandran Dorairaj; R Madhumala; Saranyan Ravi; Ann Theresa Tomy (Indian Journal of Dental Research)
Introduction: Chlorhexidine (CHX) is a chemical mouthwash that has been considered the gold standard, but has its drawbacks. When used for a longer duration, it produces taste alteration and staining on the tooth surfaces. Nowadays, herbal extracts from plants have been widely used as they possess anti-inflammatory, antimicrobial and analgesic actions. Material and Methods: A group of 45 healthy subjects in the age group of 19–35 years were selected and randomly divided into three groups, Group A - Himalaya complete care mouthwash, Group B - CHX mouthwash, Group C - Distilled water as a control group. Gingival index and plaque index, OHI-s index, and Ainamo and Bay index for bleeding were recorded. Subjects received complete supragingival scaling at baseline and were instructed to use 10 ml of mouthwashes twice a day in their group. Variables were again recorded on the seventh and 14th day after the use of mouthwashes, and data obtained was subjected to statistical analysis. Post hoc and ANOVA tests were used for statistical analysis. Results: It was found that both CHX and herbal mouthwash proved to be more effective than placebo in maintaining gingival health. There was no significant difference between the test group on gingival health. Conclusion: Herbal mouthwash is an effective alternative to CHX mouthwash, in the light of the reported side effects of CHX mouthwash.